The Role of Islamic Religious Education in the Resilience of Muslim Families during the Pandemic; The implications for the implementation of Group Guidance - Jumiarti, Desri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
ABSTRACT. Religious education is very necessary for every human being, because religion is a guide in life. This research aims to describe Islamic religious education on the resilience of Muslim families during the pandemic and its implications for the implementation of group guidance in Pantai Cermin District, Solok Regency. This research uses a quantitative approach using ex post facto or correlational methodology. The population of this research is the entire community of Pantai Cermin sub-district, Solok Regency. Jorong is divided into two categories: densely populated and sparsely populated, and sampling is done using a cluster random sampling system, by categorizing sparsely populated Jorong with densely populated ones. Several samples were selected randomly from several of these clusters. Respondents were given a questionnaire to fill out to collect data for this research. Validating the Instrument with an expert judgment system. Inferential statistical analysis techniques were used to analyze the data obtained. The R Square (R2) value is 0.262, indicating 26.2 percent of the role of Islamic religious education in family economic resilience during the pandemic. The results can be concluded that Islamic religious education, especially religious education in the family and religious discipline, plays an important role in the resilience of Muslim families in terms of legal grounds, physical, economic and social resilience during the pandemic. Apart from that, when a family is fortified with religious education, it will make the family stronger, so in this case it can have implications for the implementation of group guidance by carrying out group guidance by providing material based on religious education in increasing the family's economic resilience.